Ortodontik Tedavi Sonrası Elde Edilen Kapanışta Oklüzal Temas Noktalarlnın Komputerize Oklüzal Analiz Teknolojisi İle Değerlendirilmesi - Münire Ece Sabah; Birgül Özpınar (Galenos Yayinevi, 1996)
The occlusion reached at the end of orthodontic treatment, should be stable and functional. T-Scan occlusal analyzer is a quantitative analysis, that is used to determine occlusal contacts. This system can be used to identify premature contacts after orthodontic treatment. In this study 4 randomly selected patients recently out of orthodontic appliances, have been evaluated on the T-scan system for oclusal contacts. Our results show that occlusion evaluated sagittally and vertically is not enough for ideal occlusal results, but occlusal con-tacs should be studied as well.